Cobalt-based Fischer-Tropsch catalyst and preparation method and application thereof

By using manganese-modified composite carrier Mn-TiO2/MgO in a cobalt-based Fischer-Tropsch catalyst, the problems of insufficient stability and narrow selectivity of existing catalysts are solved, and high reaction activity, low methane selectivity and good stability are achieved. Comprehensive effect.

CN119327444AActive Publication Date: 2025-01-21PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310877303.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-01-21
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

The existing cobalt-based Fischer Tropsch catalysts are insufficient in long-term use and are difficult to take into account both high reactivity and low methane selectivity.

Method used

The manganese-modified composite carrier Mn-TiO2/MgO is used, and manganese additives are introduced into the carrier skeleton. By forming a highly dispersed manganese additive modified structure, the reduction of the cobalt phase is promoted, and the catalytic activity and selectivity are improved.

Benefits of technology

It significantly improves the reactivity and C5+ hydrocarbon selectivity of the catalyst, reduces the methane selectivity, and improves the stability of the catalyst with better adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004343977300000091
    Figure BDA0004343977300000091
  • Figure BDA0004343977300000092
    Figure BDA0004343977300000092
  • Figure BDA0004343977300000093
    Figure BDA0004343977300000093
Patent Text Reader

Abstract

The invention discloses a cobalt-based Fischer-Tropsch catalyst as well as a preparation method and application thereof. The cobalt-based Fischer-Tropsch catalyst comprises a carrier and an active component loaded on the carrier, the carrier is a composite carrier Mn-TiO2 / MgO modified by manganese; the general formula of the active component is Co < 100 > A B in terms of atomic ratio; wherein A is selected from at least one of Ru, Pt and Ir, B is selected from at least one of Zr and Nb, the value range of a is 0-5, and the value range of b is 0-15. When the cobalt-based Fischer-Tropsch catalyst is used for Fischer-Tropsch synthesis reaction, the selectivity of C5 + hydrocarbon in Fischer-Tropsch products can be improved, the cobalt-based Fischer-Tropsch catalyst has high activity and low methane selectivity, and is an efficient Fischer-Tropsch synthesis reaction catalyst, and the preparation method of the cobalt-based Fischer-Tropsch catalyst is simple and easy to industrially use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalytic synthesis gas conversion, and in particular to a cobalt-based Fischer-Tropsch catalyst and a preparation method and application thereof. Background Art

[0002] Fischer-Tropsch synthesis is a reaction that converts synthesis gas (CO+H2) into long-chain hydrocarbons, usually using a heterogeneous catalytic process. After upgrading, Fischer-Tropsch synthesis products can be upgraded to obtain clean fuels such as low-carbon olefins and liquid fuels, or high-value-added chemicals such as lubricants and solid waxes. Fischer-Tropsch synthesis catalysts mainly include iron-based and cobalt-based catalysts. Among them, cobalt-based catalysts have high activity, good stability, high conversion rate, and high hydrocarbon production rate under low temperature conditions, making them the best choice for synthesizing long-chain hydrocarbons.

[0003] The activity and product selectivity of cobalt-based catalysts generally depend on the dispersion and reduction degree of the cobalt species and the adsorption characteristics of the reactant gas on the catalyst surface. Cobalt-based catalysts are mostly supported catalysts. The difficulty lies in the reasonable combination of active components, metal additives, precious metal additives and carriers to prepare high-performance Fischer-Tropsch synthesis catalysts, thereby achieving good industrial applications. Adding a second metal to modify the catalyst is one of the effective ways to regulate the structure of the catalyst and the catalytic reaction performance.

[0004] Dinse et al. (Dinse A, Aigner M, Ulbrich M, et al. Effects of Mn promotion on the activity and selectivity of Co / SiO2 for Fischer–Tropsch Synthesis [J]. Journal of Catalysis, 2012, 288: 104-114.) used an equal volume impregnation method to impregnate a silica support with a pore size of 27 nm using a cobalt nitrate solution and a manganese acetate solution, and added a small amount of Mn to the Co / SiO2 catalyst. The study found that at 1 atm (Mn / Co = 0.05), the addition of Mn increased the CO consumption rate, inhibited the formation of CH4, and the C 5+ The selectivity of hydrocarbons increased, but the selectivity of C2-C4 products was not affected. When the pressure was increased to 10 atm, the CO consumption rate of the catalyst Co / SiO2 without and with Mn increased, but the reaction rate of the catalyst with Mn was lower due to the higher CO inhibition. In addition, this method only conducted a short-term stability evaluation, and no long-term evaluation results were obtained, so it cannot be seen that the catalyst has good stability.

[0005] Morales et al. (Morales F, Degroot F, Gijzeman O, et al. Mn promotion effects in Co / TiO2 Fischer-Tropsch catalysts as investigated by XPS and STEM-EELS [J]. Journal of Catalysis, 2005, 230 (2): 301-308.) modified Co / TiO2 with a small amount of Mn, which increased the FTS activity and suppressed the CH4 yield. The characterization results showed that the calcined catalyst had obvious Co-Mn interaction, which may promote the formation of solid solution spinel compounds and increase the difficulty of reducing cobalt species.

[0006] Zhang et al. (Zhang Qingling, Guo Heqin, Bo Hou, et al. Effects of Mn and Zr additives on the Fischer-Tropsch synthesis performance of mesoporous carbon-supported cobalt-based catalysts [J]. Journal of Fuel Chemistry and Technology, 2017, 45(6): 682-688.) prepared mesoporous carbon-supported cobalt-based catalysts modified by manganese and zirconium by impregnation. The addition of manganese or zirconium additives reduced the selectivity of methane. Among them, the addition of manganese additives increased the selectivity of C 2-4 The addition of zirconium improves the dispersion of cobalt species and increases the reactive sites, which significantly improves the Fischer-Tropsch reaction activity and C 5+ Selectivity. This modification method has made significant progress in improving the activity and product selectivity of cobalt-based Fischer-Tropsch synthesis catalysts, but it does not take into account all aspects of performance at the same time. In addition, most catalysts have a narrow selectivity temperature and poor catalyst adaptability. In addition, there are no long-term evaluation results, and it cannot be seen that the catalyst has good stability.

[0007] CN107617442A discloses a precipitated iron-based catalyst for Fischer-Tropsch synthesis containing a manganese additive, and uses it in a Fischer-Tropsch synthesis slurry bed reactor. It is found that the catalyst can increase the CO conversion rate and reduce the selectivity of methane and carbon dioxide.

[0008] CN113117689A discloses a cobalt-based Fischer-Tropsch synthesis catalyst containing a manganese additive, a preparation method thereof, and an application thereof in a Fischer-Tropsch synthesis reaction. The carrier used is a cobalt aluminum spinel carrier, which is modified by adding a manganese oxide additive. The cobalt aluminum spinel carrier has a high reduction temperature, which easily leads to insufficient reduction of cobalt species.

[0009] Han et al. (Effect of support modification and precursor decomposition method on the properties of CoPt / ZrO2 Fischer-Tropsch catalysts[J].Catalysis Today, 2021, 375(1).) prepared a series of CoPt / ZrO2 catalysts using plasma treatment to modify the ZrO2 support and / or decompose cobalt, which changed the support morphology. When the synergistic effect of plasma modification of the support and precursor decomposition resulted in highly dispersed cobalt species (~1nm), these highly dispersed cobalt particles also had better reduction ability, but their TOF values ​​were lower. Summary of the invention

[0010] The first object of the present invention is to provide a cobalt-based Fischer-Tropsch catalyst.

[0011] The second object of the present invention is to provide a method for preparing the cobalt-based Fischer-Tropsch catalyst.

[0012] The third object of the present invention is to provide an application of the cobalt-based Fischer-Tropsch catalyst in Fischer-Tropsch synthesis.

[0013] The catalyst provided by the present invention can increase the C 5+ hydrocarbons and has the characteristic of low methane selectivity.

[0014] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0015] In one aspect, the present invention provides a cobalt-based Fischer-Tropsch catalyst, wherein the cobalt-based Fischer-Tropsch catalyst comprises a carrier and an active component supported on the carrier;

[0016] The carrier is a manganese-modified composite carrier Mn-TiO2 / MgO;

[0017] The active component is generally represented by the atomic ratio: Co 100 A a B b ; wherein A is selected from at least one of Ru, Pt, and Ir, B is selected from at least one of Zr and Nb, the value range of a is 0 to 5, and the value range of b is 0 to 15.

[0018] In some specific embodiments of the present invention, in the cobalt-based Fischer-Tropsch catalyst, the mass proportion of the active component is 20% to 50%, and the mass proportion of the carrier is 50% to 80%.

[0019] In some specific embodiments of the present invention, in the cobalt-based Fischer-Tropsch catalyst, the mass proportion of the active component is 20% to 35%, and the mass proportion of the carrier is 65% to 80%.

[0020] In some specific embodiments of the present invention, in the manganese-modified composite support Mn-TiO2 / MgO, the molar ratio of manganese to magnesium is 1:(0.1-25), and the molar ratio of manganese to titanium is 1:(0.1-25).

[0021] In some specific embodiments of the present invention, in the manganese-modified composite support Mn-TiO2 / MgO, the molar ratio of manganese to magnesium is 1:(1-15), and the molar ratio of manganese to titanium is 1:(1-15).

[0022] In some specific embodiments of the present invention, the active component Co 100 A a B b In the formula, the value range of a is 0.1 to 2, and the value range of b is 5 to 10.

[0023] In some specific embodiments of the present invention, the active component Co 100 A a B b In the formula, the value of a ranges from 0.3 to 1.

[0024] In some specific embodiments of the present invention, the specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 80 to 220 m 2 / g, preferably 96 to 209 m 2 / g; pore volume is 0.2~0.7cm 3 / g, preferably 0.24 to 0.65 cm 3 / g; the pore diameter is 5 to 35 nm, preferably 8 to 30 nm.

[0025] In some specific embodiments of the present invention, the carrier is prepared by the following steps:

[0026] Dissolving a manganese source, a magnesium source and a titanium source in an alcohol solvent to obtain a mixed solution A;

[0027] After adding mesoporous silica to the mixed solution A, heating and stirring to form a mixture B;

[0028] Adding an epoxy compound to the mixture B, stirring until the mixture becomes a gel, and then aging the mixture;

[0029] drying and calcining the mixture obtained by aging;

[0030] The calcined solid is treated with a hot alkaline solution and centrifuged to obtain a solid C;

[0031] Dissolve tetraethyl orthosilicate in an alcohol solvent to form a mixed solution D; then mix the mixed solution D with a solid substance C for immersion, and then dry and calcine to obtain a manganese-modified composite support Mn-TiO2 / MgO.

[0032] The alcohol solvent is preferably at least one of ethanol, ethylene glycol or glycerol; the alcohol solvent also serves as a dispersant and a stabilizer, and is preferably ethanol.

[0033] The mesoporous silicon oxide is used as a template for forming non-silicon-based mesoporous materials, preferably SBA-15 or KIT-6. The molar number of the mesoporous silicon oxide is preferably 3 to 4 times the total molar number of the metal elements.

[0034] The epoxy compound acts as a gel accelerator, taking away protons in the system and promoting the hydrolysis and polymerization of hydrated metal ions; the epoxy compound is preferably selected from propylene oxide, methyl propylene oxide and the like.

[0035] The tetraethyl orthosilicate acts as a surface modifier, condenses with hydroxyl groups in the skeleton, reduces the stress formed by dehydration condensation between hydroxyl groups in the pores, enhances the strength of the skeleton, and consumes part of the hydroxyl groups and the remaining water on the surface.

[0036] After calcination, the silicon oxide is removed by treatment with a hot alkaline solution, such as a sodium hydroxide solution at 75 to 100° C., for example, a sodium hydroxide solution at 80° C. used in the examples.

[0037] In some specific embodiments of the present invention, after adding mesoporous silica to the mixed solution A, the mixture is heated to 60-85° C. and stirred for 4-6 hours to form the mixture B.

[0038] In some specific embodiments of the present invention, the aging is carried out in a water bath at 60-85°C.

[0039] In some specific embodiments of the present invention, the manganese source is selected from at least one of manganese nitrate and manganese acetate.

[0040] In some specific embodiments of the present invention, the manganese source is manganese nitrate.

[0041] In some specific embodiments of the present invention, the magnesium source is selected from at least one of magnesium nitrate, magnesium acetate and magnesium chloride.

[0042] In some specific embodiments of the present invention, the magnesium source is magnesium nitrate.

[0043] In some specific embodiments of the present invention, the titanium source is selected from at least one of titanium sulfate, butyl titanate, tetraisopropyl titanate, and titanium chloride.

[0044] In some specific embodiments of the present invention, the titanium source is titanium sulfate.

[0045] In some specific embodiments of the present invention, in the solution A, the molar number of the alcohol solvent is 1 to 40 times the total molar number of the added metal elements.

[0046] In some specific embodiments of the present invention, in the solution C, the molar number of the alcohol solvent is 1 to 40 times the molar number of the added tetraethyl orthosilicate.

[0047] In some specific embodiments of the present invention, the molar number of the epoxy compound is 1 to 15 times the total molar number of the added metal elements.

[0048] In some specific embodiments of the present invention, the molar number of the epoxy compound is 4 to 10 times the total molar number of the added metal elements.

[0049] In some specific embodiments of the present invention, the drying temperature of the aging mixture is 60-120°C, and the drying time is 6-24 hours; the calcination temperature is 550-750°C, and the calcination time is 2-4 hours; for example, the calcination temperature is 600°C, and the heating rate can be 1°C / min, etc.

[0050] In some specific embodiments of the present invention, the mixed solution D is used to soak the solid object C for 1 to 3 times, each time for 3 to 6 hours.

[0051] In some specific embodiments of the present invention, the soaked solid C is dried at a temperature of 60-120° C. for 4-24 hours, and is calcined at a temperature of 400-750° C. for 3-12 hours.

[0052] Another aspect of the present invention provides a method for preparing any one of the above cobalt-based Fischer-Tropsch catalysts, wherein the preparation method comprises the following steps:

[0053] Dissolve the soluble salt containing the active ingredient in deionized water to prepare a mixed solution I with a volume equal to or in excess of the water absorption of the carrier;

[0054] The mixed solution I is added dropwise onto the support to form a mixture I, which is allowed to stand for drying and calcination to obtain the cobalt-based Fischer-Tropsch catalyst.

[0055] The water absorption of the carrier is obtained by testing the water absorption rate of the carrier in advance.

[0056] In some specific embodiments of the present invention, the mixture I is formed and then allowed to stand for 12 to 24 hours.

[0057] In some specific embodiments of the present invention, the cobalt source in the soluble salt containing the active component is selected from at least one of cobalt nitrate, cobalt acetate, cobalt carbonate, cobalt bicarbonate and cobalt sulfate.

[0058] In some specific embodiments of the present invention, the cobalt source in the soluble salt containing the active ingredient is cobalt nitrate.

[0059] In some specific embodiments of the present invention, when the active component further includes A metal and / or B metal, the soluble salt containing the active component further includes nitrate, chloride or oxalate of A metal and / or B metal.

[0060] In some specific embodiments of the present invention, when the active component also includes A metal and / or B metal, the soluble salt containing the active component also includes at least one of the following: ruthenium trichloride, chloroplatinic acid, hydrated iridium trichloride, zirconium nitrate pentahydrate, niobium oxalate.

[0061] In some specific embodiments of the present invention, the drying temperature of the mixture I after standing is 80-120° C., and the drying time is 6-24 hours.

[0062] In some specific embodiments of the present invention, the calcination temperature of the dried mixture I is 450-600° C., and the calcination time is 2-4 hours.

[0063] In another aspect, the present invention provides a use of any one of the above cobalt-based Fischer-Tropsch catalysts in a Fischer-Tropsch synthesis reaction, wherein the cobalt-based Fischer-Tropsch catalyst is reduced and activated by hydrogen-containing gas before use.

[0064] In some specific embodiments of the present invention, the Fischer-Tropsch synthesis reaction is carried out in a fixed bed reactor, and the reaction conditions include: reaction temperature of 200-260°C, raw gas V(H2) / V(CO)=1.5-3, reaction pressure of 1.5-3MPa, space velocity of 800-2000h -1 .

[0065] The present invention uses the composite oxide Mn-TiO2 / MgO as a carrier, and its mesoporous structure has a large specific surface area and a smaller grain size, which produces more lattice defects. Different from the conventional impregnation method to introduce manganese additives into the catalyst active components, the present invention introduces manganese additives into the carrier skeleton, so that the manganese additives exist in the skeleton in a highly dispersed form, and it is modified on the composite carrier. It can not only act as a structural additive to promote the dispersion of the active phase, but also act as an electronic additive to provide electrons to the cobalt phase to promote the reduction of the catalyst, thereby affecting the properties of the loaded active metal. In addition, the mild Co-Ti interaction formed by the composite carrier and the cobalt component is conducive to the reduction of cobalt oxides, so that the catalytic activity is significantly improved, which has the advantages of improving the catalyst reaction activity and increasing the C in the Fischer-Tropsch product.5+ At the same time, by adding various effective additives, the adsorption and activation of carbon monoxide and hydrogen are enhanced, the reduction of Co is promoted, and high activity and C can be maintained at a lower reaction temperature. 5+ Hydrocarbon selectivity can effectively prevent carbon deposition at high temperatures, thereby improving catalyst stability.

[0066] When the cobalt-based Fischer-Tropsch catalyst of the present invention is used in the Fischer-Tropsch synthesis reaction, the C 5+ It is hydrocarbon selective, has high activity and low methane selectivity, is an efficient Fischer-Tropsch synthesis catalyst, and its preparation method is simple and easy to use in industrialization. DETAILED DESCRIPTION

[0067] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0068] The key to the cobalt-based Fischer-Tropsch catalyst of the present invention is that it uses the composite oxide Mn-TiO2 / MgO as a carrier, and its mesoporous structure has a large specific surface area and a smaller grain size, which produces more lattice defects. Different from the conventional impregnation method to introduce manganese additives into the catalyst active components, the present invention introduces manganese additives into the carrier skeleton, so that the manganese additives can exist in the skeleton in a highly dispersed form, and it is modified on the composite carrier, which can not only act as a structural additive to promote the dispersion of the active phase, but also act as an electronic additive to provide electrons to the cobalt phase to promote the reduction of the catalyst, thereby affecting the properties of the loaded active metal. In addition, the mild Co-Ti interaction formed by the composite carrier and the cobalt component is conducive to the reduction of cobalt oxides, so that the catalytic activity is significantly improved, which has the advantages of improving the catalyst reaction activity and increasing the C content in the Fischer-Tropsch product. 5+ At the same time, by adding various effective additives, the adsorption and activation of carbon monoxide and hydrogen are enhanced, the reduction of Co is promoted, and high activity and C can be maintained at a lower reaction temperature. 5+ Hydrocarbon selectivity can effectively prevent carbon deposition at high temperatures, thereby improving catalyst stability.

[0069] Specifically, the cobalt-based Fischer-Tropsch catalyst provided by the present invention comprises a carrier and an active component loaded on the carrier; the carrier is a manganese-modified composite carrier Mn-TiO2 / MgO; the active component has a general formula in terms of atomic ratio: Co 100 A a B b ; wherein A is selected from at least one of Ru, Pt, and Ir, B is selected from at least one of Zr and Nb, the value range of a is 0 to 5, and the value range of b is 0 to 15.

[0070] In some specific embodiments of the present invention, in the cobalt-based Fischer-Tropsch catalyst, the mass proportion of the active component is 20% to 50%, and the mass proportion of the carrier is 50% to 80%. Preferably, the mass proportion of the active component is 20% to 35%, and the mass proportion of the carrier is 65% to 80%.

[0071] In some specific embodiments of the present invention, in the manganese-modified composite support Mn-TiO2 / MgO, the molar ratio of manganese to magnesium is 1:(0.1-25), and the molar ratio of manganese to titanium is 1:(0.1-25). Preferably, in the manganese-modified composite support Mn-TiO2 / MgO, the molar ratio of manganese to magnesium is 1:(1-15), and the molar ratio of manganese to titanium is 1:(1-15).

[0072] In some specific embodiments of the present invention, the active component Co 100 A a B b In the above, the value range of a is 0.1 to 2, and the value range of b is 5 to 10. Preferably, the value range of a is 0.3 to 1.

[0073] In some specific embodiments of the present invention, the specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is preferably 80 to 220 m 2 / g, preferably 96 to 209 m 2 / g; pore volume is 0.2~0.7cm 3 / g, preferably 0.24 to 0.65 cm 3 / g; the pore diameter is 5 to 35 nm, preferably 8 to 30 nm.

[0074] The carrier of the catalyst of the present invention is prepared by the following steps:

[0075] Dissolving a manganese source, a magnesium source and a titanium source in an alcohol solvent to obtain a mixed solution A;

[0076] After adding mesoporous silica to the mixed solution A, heating and stirring to form a mixture B;

[0077] Adding an epoxy compound to the mixture B, stirring until the mixture becomes a gel, and then aging the mixture;

[0078] drying and calcining the mixture obtained by aging;

[0079] The calcined solid is treated with a hot alkaline solution and centrifuged to obtain a solid C;

[0080] Ethyl orthosilicate is dissolved in an alcohol solvent to form a mixed solution D; the mixed solution D is then added to the solid C for soaking, followed by drying and calcining to obtain a manganese-modified composite support Mn-TiO2 / MgO.

[0081] In the preparation process of the carrier, the manganese source is selected from at least one of manganese nitrate and manganese acetate, preferably manganese nitrate. The magnesium source is selected from at least one of magnesium nitrate, magnesium acetate and magnesium chloride, preferably magnesium nitrate. The titanium source is selected from at least one of titanium sulfate, butyl titanate, tetraisopropyl titanate and titanium chloride, preferably titanium sulfate.

[0082] The alcohol solvent is preferably selected from at least one of ethanol, ethylene glycol or glycerol; the alcohol solvent also has the functions of a dispersant and a stabilizer, preferably ethanol. In the solution A, the molar number of the alcohol solvent is preferably 1 to 40 times the total molar number of the added metal elements. After adding mesoporous silica to the mixed solution A, it is preferably heated to 60 to 85°C and stirred for 4 to 6 hours to form solution B. In the solution C, the molar number of the alcohol solvent is preferably 1 to 40 times the molar number of the added tetraethyl orthosilicate. The epoxy compound acts as a gel promoter, captures protons in the system, and promotes the hydrolysis and polymerization reaction of hydrated metal ions; the epoxy compound is preferably selected from propylene oxide, methyl propylene oxide, etc. The molar number of the epoxy compound is preferably 1 to 15 times the total molar number of the added metal elements, and more preferably 4 to 10 times. Aging is preferably carried out in a water bath at 60 to 85°C, the drying temperature of the aging mixture is preferably 60 to 120°C, and the drying time is preferably 6 to 24 hours; the calcination temperature is preferably 550 to 750°C, and the calcination time is preferably 2 to 4 hours; for example, the calcination temperature is 600°C, and the heating rate can be 1°C / min, etc. The solid C is preferably soaked 1 to 3 times using the mixed solution D, each time for 3 to 6 hours. The temperature for drying the soaked solid C is preferably 60 to 120°C, and the drying time is preferably 4 to 24 hours. The roasting temperature is preferably 400 to 750°C, and the roasting time is preferably 3 to 12 hours.

[0083] The mesoporous silicon oxide is used as a template for forming non-silicon-based mesoporous materials, preferably SBA-15 or KIT-6. The molar number of the mesoporous silicon oxide is preferably 3 to 4 times the total molar number of the metal elements.

[0084] The tetraethyl orthosilicate acts as a surface modifier, condenses with the hydroxyl groups in the skeleton, reduces the stress formed by the dehydration condensation between the hydroxyl groups in the pores, enhances the strength of the skeleton, and consumes part of the hydroxyl groups on the surface and the remaining water. After calcination, a hot alkaline solution is used to remove silicon oxide, and the hot alkaline solution is, for example, a sodium hydroxide solution at 75 to 100° C., more specifically, a sodium hydroxide solution at 80° C. used in the embodiment.

[0085] The preparation method of the cobalt-based Fischer-Tropsch catalyst of the present invention comprises the following steps:

[0086] Dissolve the soluble salt containing the active ingredient in deionized water to prepare a mixed solution I with a volume equal to or in excess of the water absorption of the carrier;

[0087] The mixed solution I is added dropwise onto the support to form a mixture I, which is allowed to stand for drying and calcination to obtain the cobalt-based Fischer-Tropsch catalyst.

[0088] The water absorption of the carrier is obtained by testing the water absorption rate of the carrier in advance.

[0089] In the preparation process of the catalyst, the cobalt source in the soluble salt containing the active component is preferably selected from at least one of cobalt nitrate, cobalt acetate, cobalt carbonate, cobalt bicarbonate, and cobalt sulfate, and is more preferably cobalt nitrate. In addition, when the active component also includes A metal and / or B metal, the soluble salt containing the active component also includes nitrate, chloride or oxalate of A metal and / or B metal. More preferably, when the active component also includes A metal and / or B metal, the soluble salt containing the active component also includes at least one of the following: ruthenium trichloride, chloroplatinic acid, hydrated iridium trichloride, zirconium nitrate pentahydrate, niobium oxalate.

[0090] The drying temperature of the mixture I after standing is preferably 80 to 120° C., and the drying time is preferably 6 to 24 hours. The calcination temperature of the dried mixture I is preferably 450 to 600° C., and the calcination time is preferably 2 to 4 hours. The standing time is preferably 12 to 24 hours.

[0091] The cobalt-based Fischer-Tropsch catalyst of the present invention is applied to the Fischer-Tropsch synthesis reaction, and the cobalt-based Fischer-Tropsch catalyst is activated by reduction with hydrogen-containing gas before use. Preferably, the Fischer-Tropsch reaction is carried out in a fixed bed reactor, and the reaction conditions include: reaction temperature of 200-260°C, raw gas V(H2) / V(CO)=1.5-3, reaction pressure of 1.5-3MPa, and space velocity of 800-2000h -1 .

[0092] When the cobalt-based Fischer-Tropsch catalyst of the present invention is used in the Fischer-Tropsch synthesis reaction, the C 5+ It is hydrocarbon selective, has high activity and low methane selectivity, is an efficient Fischer-Tropsch synthesis catalyst, and its preparation method is simple and easy to use in industrialization.

[0093] The present invention is described in more detail below with some specific examples, in which all numerical values ​​(such as temperature, time, concentration and weight, etc., including the range of each thereof) are usually appropriately changed by (+) or (-) approximate values ​​in increments of 0.1 or 1.0. All numerical values ​​are understood to be preceded by the term "about".

[0094] The conversion rate of the FTS reaction can be calculated based on a single reaction component. The CO conversion rate is used in the present invention. In the embodiment, the conversion rate and selectivity are calculated by the following formulas:

[0095]

[0096]

[0097]

[0098] Wherein, A is the peak area of ​​the gas detected by the TCD detector;

[0099] C m is the C content of each substance;

[0100] X CO is the conversion rate of carbon monoxide;

[0101] S is the selectivity of each substance.

[0102] Example 1

[0103] This embodiment prepares a composite carrier Mn-TiO2 / MgO (Z1), comprising the following steps:

[0104] 1) Weigh 0.358 g of manganese nitrate (50 wt%), weigh the corresponding magnesium nitrate and titanium sulfate according to the metal element molar ratio of manganese to magnesium being 1:25 and the metal element molar ratio of manganese to titanium being 1:6, stir them thoroughly to dissolve them and mix and dissolve them in 2.81 g of anhydrous ethanol to obtain a mixed solution A.

[0105] 2) After adding 6 g of KIT-6 to the mixed solution A, the mixture was stirred at 65° C. for 4 h to form a mixture B.

[0106] 3) Add 14.15 g of propylene oxide to mixture B (Note: the molar number of propylene oxide is 4 times the total molar number of the added metal elements), stir thoroughly until it becomes a gel, and carry out an aging process in a water bath at 65°C.

[0107] 4) The mixture was transferred to a drying oven at 100°C for 12 h, and then calcined at 600°C for 3 h with a heating rate of 1°C / min.

[0108] 5) The obtained solid was treated with 2 mol / L sodium hydroxide solution at 80°C and centrifuged to obtain solid C.

[0109] 6) Add 16.25 g of ethyl orthosilicate to 27.6 g of anhydrous ethanol, stir thoroughly to dissolve, add to solid C, and soak for 3 times, each time for 5 hours; then dry at 100°C for 12 hours, and calcine at 540°C for 4 hours to finally obtain a composite carrier Mn-TiO2 / MgO, denoted as Z1.

[0110] Example 2

[0111] This embodiment prepares a composite carrier Mn-TiO2 / MgO (Z2), and the preparation process is different from that of Example 1 in that:

[0112] The mass of manganese nitrate (50wt%) is 0.537g, the metal element molar ratio of manganese and magnesium is 1:1, the metal element molar ratio of manganese and titanium is 1:25, KIT-6 is replaced by SBA-15, and the molar number of propylene oxide is 7 times the total molar number of the added metal elements; in step 2), stirring at 60°C for 6h to form a mixture B; in step 3), the aging temperature is 60°C; in step 4), the mixture is transferred to a 120°C drying oven and dried for 6h, and then calcined at 550°C for 4h; in step 6), after soaking, dried at 60°C for 24h, and calcined at 750°C for 3h.

[0113] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z2.

[0114] Example 3

[0115] This example prepares a composite carrier Mn-TiO2 / MgO (Z3), and the preparation process is different from that of Example 1 in that:

[0116] The mass of manganese nitrate (50wt%) is 0.215g, the molar ratio of metal elements of manganese and magnesium is 1:5, the molar ratio of metal elements of manganese and titanium is 1:5, and the molar number of propylene oxide is 10 times the total molar number of the added metal elements. In step 2), stirring is performed at 80°C for 4 hours to form a mixture B; in step 3), the aging temperature is 60°C; in step 4), the mixture is transferred to an 80°C drying oven and dried for 14 hours, and then calcined at 600°C for 4 hours; in step 6), after soaking, it is dried at 120°C for 4 hours and calcined at 700°C for 5 hours.

[0117] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z3.

[0118] Example 4

[0119] This example prepares a composite carrier Mn-TiO2 / MgO (Z4), and the preparation process is different from that of Example 1 in that:

[0120] The mass of manganese nitrate (50wt%) is 0.358g. The molar ratio of metal elements of manganese and magnesium is 1:15, the molar ratio of metal elements of manganese and titanium is 1:10, and the molar number of propylene oxide is 15 times the total molar number of the added metal elements. In step 2), stirring is performed at 60°C for 5 hours to form a mixture B; in step 3), the aging temperature is 85°C; in step 4), the mixture is transferred to a drying oven at 90°C and dried for 12 hours, and then calcined at 750°C for 3 hours; in step 6), after soaking, it is dried at 80°C for 10 hours and calcined at 600°C for 10 hours.

[0121] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z4.

[0122] Example 5

[0123] This example prepares a composite carrier Mn-TiO2 / MgO (Z5), and the preparation process is different from that of Example 1 in that:

[0124] The mass of manganese nitrate (50wt%) is 0.358g, the molar ratio of metal elements of manganese and magnesium is 1:10, the molar ratio of metal elements of manganese and titanium is 1:5, and the molar number of propylene oxide is 8 times the total molar number of the added metal elements. In step 2), stirring is performed at 85°C for 4 hours to form a mixture B; in step 3), the aging temperature is 75°C; in step 4), the mixture is transferred to a 60°C drying oven and dried for 24 hours, and then calcined at 650°C for 4 hours; in step 6), after soaking, it is dried at 90°C for 10 hours and calcined at 500°C for 12 hours.

[0125] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z5.

[0126] Example 6

[0127] This example prepares a composite carrier Mn-TiO2 / MgO (Z6), and the preparation process is different from that of Example 1 in that:

[0128] The mass of manganese acetate is 0.26g, the metal element molar ratio of manganese and magnesium (the precursor is magnesium acetate) is 1:0.1, the metal element molar ratio of manganese and titanium (the precursor is butyl titanate) is 1:15, and the molar number of propylene oxide is 6 times the total molar number of the added metal elements. In step 2), the mixture is stirred at 70°C for 6 hours to form a mixture B; in step 3), the aging temperature is 70°C; in step 4), the mixture is transferred to a 100°C drying oven and dried for 12 hours, and then calcined at 700°C for 2 hours; in step 6), after soaking, it is dried at 100°C for 10 hours and calcined at 550°C for 12 hours.

[0129] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z6.

[0130] Example 7

[0131] This example prepares a composite carrier Mn-TiO2 / MgO (Z7), and the preparation process is different from that of Example 1 in that:

[0132] The mass of manganese nitrate (50wt%) is 0.537g, the metal element molar ratio of manganese to magnesium (the precursor is magnesium chloride) is 1:13, the metal element molar ratio of manganese to titanium (the precursor is tetraisopropyl titanate) is 1:1, and the molar number of propylene oxide is 3 times the total molar number of the added metal elements. In step 2), the mixture is stirred at 70°C for 6h to form a mixture B; in step 3), the aging temperature is 70°C; in step 4), the mixture is transferred to a drying oven at 110°C and dried for 20h, and then calcined at 600°C for 4h.

[0133] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z7.

[0134] Example 8

[0135] This example prepares a composite carrier Mn-TiO2 / MgO (Z8), and the preparation process is different from that of Example 1 in that:

[0136] The mass of manganese nitrate (50wt%) is 0.537g, the metal element molar ratio of manganese to magnesium is 1:20, the metal element molar ratio of manganese to titanium (the precursor is titanium chloride) is 1:0.1, and the molar number of propylene oxide is 11 times the total molar number of the added metal elements. In step 2), stirring is performed at 75°C for 5h to form a mixture B; in step 3), the aging temperature is 75°C; in step 4), the mixture is transferred to a drying oven at 70°C and dried for 24h, and then calcined at 650°C for 4h.

[0137] The other conditions were the same as those in Example 1, and a composite carrier Mn-TiO2 / MgO was obtained, which was denoted as Z8.

[0138] Example 9

[0139] In this example, the catalyst 30% Co was prepared using carrier Z1 100 -70% Z1, and conduct catalytic evaluation on the catalyst, including the following processes:

[0140] 1) 147.8 g of cobalt nitrate hexahydrate was dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 70 g of the carrier Z1 prepared in Example 1 to form a mixture I, which was allowed to stand for 18 h.

[0141] 2) The mixture I was transferred to a drying oven at 100°C and dried for 12 hours, and then calcined at 540°C for 4 hours to obtain a catalyst with 30% Co100 -70% Z1, wherein 30% and 70% represent the ratio of active component to carrier respectively, and the subscript in the active component represents the content ratio of each element in the active component.

[0142] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 120 m 2 / g, pore volume is 0.65cm 3 / g, pore size is 8nm.

[0143] 3) Catalyst evaluation in a fixed bed reactor:

[0144] First, pure hydrogen was introduced to reduce and activate the catalyst at a reduction temperature of 430°C, a pressure of 2.5 MPa, and a space velocity of 1000 h -1 , the reduction time is 8h.

[0145] The reaction conditions are: reaction temperature 216°C, raw gas V(H2) / V(CO)=2, reaction pressure 2.5MPa, space velocity 1000h -1 After the reaction stabilized, samples were taken for analysis. The catalyst evaluation results are shown in Table 1.

[0146] Example 10

[0147] In this example, the catalyst 30% Co was prepared using carrier Z2 100 Ru1-70% Z2, and the catalyst was evaluated for catalysis, including the following processes:

[0148] 1) 145.5 g of cobalt nitrate hexahydrate and 1.04 g of ruthenium trichloride were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 70 g of the carrier Z2 prepared in Example 2 to form a mixture I, which was allowed to stand for 12 h.

[0149] 2) The mixture I was transferred to a drying oven at 80°C and dried for 24 hours, and then calcined at 600°C for 2 hours to obtain a catalyst with 30% Co 100 Ru1-70% Z2.

[0150] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 209 m 2 / g, pore volume is 0.3cm 3 / g, pore size is 13nm.

[0151] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0152] Embodiment 11

[0153] In this example, the catalyst 30% Co was prepared using carrier Z3 100 Pt 0.5-70% Z3, and conduct catalytic evaluation on the catalyst, including the following processes:

[0154] 1) 145.5 g of cobalt nitrate hexahydrate and 1.025 g of chloroplatinic acid were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 70 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 24 h.

[0155] 2) The mixture I was transferred to a drying oven at 120°C and dried for 6 hours, and then calcined at 450°C for 4 hours to obtain a catalyst with 30% Co 100 Pt 0.5 -70% Z3.

[0156] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 146 m 2 / g, pore volume is 0.47cm 3 / g, pore size is 26nm.

[0157] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0158] Example 12

[0159] In this example, the catalyst 30% Co was prepared using carrier Z4 100 Ir2-70% Z4, and the catalyst was evaluated for catalysis, including the following processes:

[0160] 1) 138.9 g of cobalt nitrate hexahydrate and 3.35 g of hydrated iridium trichloride were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 70 g of the carrier Z4 prepared in Example 4 to form a mixture I, which was allowed to stand for 18 h.

[0161] 2) The mixture I was transferred to a drying oven at 100°C and dried for 12 hours, and then calcined at 540°C for 4 hours to obtain a catalyst with 30% Co 100 Ir2-70% Z4.

[0162] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 182 m 2 / g, pore volume is 0.51cm 3 / g, pore size is 12nm.

[0163] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0164] Embodiment 13

[0165] In this example, the catalyst 35% Co was prepared using carrier Z5 100 Pt 0.3 Zr 10-65% Z5, and conduct catalytic evaluation on the catalyst, including the following processes:

[0166] 1) 148.41 g of cobalt nitrate hexahydrate, 0.627 g of chloroplatinic acid and 21.90 g of zirconium nitrate pentahydrate were dissolved in 100 ml of water to prepare a solution of a certain concentration, and then added dropwise to 65 g of the carrier Z5 prepared in Example 5 to form a mixture I, which was allowed to stand for 18 h.

[0167] 2) Transfer the mixture I to a 100°C drying oven and dry for 12 h, then calcine at 540°C for 4 h to obtain a catalyst 35% Co 100 Pt 0.3 Zr 10 -65% Z5.

[0168] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 177 m 2 / g, pore volume is 0.27cm 3 / g, pore size is 26nm.

[0169] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0170] Embodiment 14

[0171] In this example, the catalyst 35% Co was prepared using carrier Z6 100 Ru 0.1 Zr 15 -65% Z6, and conduct catalytic evaluation on the catalyst, including the following processes:

[0172] 1) 140.00 g of cobalt nitrate hexahydrate, 0.1 g of ruthenium trichloride and 30.98 g of zirconium nitrate pentahydrate were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 65 g of the carrier Z6 prepared in Example 6 to form a mixture I, which was allowed to stand for 18 h.

[0173] 2) Transfer the mixture I to a 100°C drying oven and dry for 12 h, then calcine at 540°C for 4 h to obtain a catalyst 35% Co 100 Ru 0.1 Zr 15 -65% Z6.

[0174] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 150 m 2 / g, pore volume is 0.44cm 3 / g, pore size is 16nm.

[0175] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0176] Embodiment 15

[0177] In this example, the catalyst 20% Co was prepared using carrier Z7 100 Ru5Zr5Nb8-80%Z7, and the catalyst was evaluated for catalysis, including the following processes:

[0178] 1) 76.53 g of cobalt nitrate hexahydrate, 2.73 g of ruthenium trichloride, 5.65 g of zirconium nitrate pentahydrate and 11.30 g of niobium oxalate were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 80 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 18 h.

[0179] 2) The mixture I was transferred to a drying oven at 100°C and dried for 12 h, and then calcined at 540°C for 4 h to obtain a catalyst 20% Co 100 Ru5Zr5Nb8-80%Z7.

[0180] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 164 m 2 / g, pore volume is 0.41cm 3 / g, pore size is 22nm.

[0181] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0182] Example 16

[0183] In this example, the catalyst 35% Co was prepared using carrier Z8 100 Ru1Ir2Zr7-65%Z8, and the catalyst was evaluated for catalysis, including the following processes:

[0184] 1) 145.03 g of cobalt nitrate hexahydrate, 1.034 g of ruthenium trichloride, 14.98 g of zirconium nitrate pentahydrate, and 6.76 g of hydrated iridium trichloride were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 80 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 18 h.

[0185] 2) Transfer the mixture I to a 100°C drying oven and dry for 12 h, then calcine at 540°C for 4 h to obtain a catalyst 35% Co 100 Ru1Ir2Zr7-65%Z8.

[0186] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 131 m 2 / g, pore volume is 0.24cm 3 / g, pore size is 30nm.

[0187] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0188] Embodiment 17

[0189] In this example, the catalyst 35% Co was prepared using carrier Z3 100 Pt 0.5 Nb8-65% Z3, and the catalyst was evaluated for catalysis, including the following processes:

[0190] 1) 151.03 g of cobalt nitrate hexahydrate, 1.066 g of chloroplatinic acid and 22.38 g of niobium oxalate were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 65 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 18 h.

[0191] 2) Transfer the mixture I to a 100°C drying oven and dry for 12 h, then calcine at 540°C for 4 h to obtain a catalyst 35% Co 100 Pt 0.5 Nb8-65%Z3.

[0192] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 146 m 2 / g, pore volume is 0.46cm 3 / g, pore size is 23nm.

[0193] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0194] Embodiment 18

[0195] In this example, the catalyst 50% Co was prepared using carrier Z3 100 Pt 0.3 Nb5Zr5-50%Z3, and the catalyst was evaluated for catalysis, including the following processes:

[0196] 1) 211.557 g of cobalt nitrate hexahydrate, 0.8938 g of chloroplatinic acid, 19.56 g of niobium oxalate and 15.6 g of zirconium nitrate pentahydrate were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 50 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 18 h.

[0197] 2) The mixture I was transferred to a drying oven at 100°C and dried for 12 h, and then calcined at 540°C for 4 h to obtain a catalyst 50% Co 100 Pt 0.3 Nb5Zr5-50%Z3.

[0198] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 96 m 2 / g, pore volume is 0.42cm 3 / g, pore size is 27nm.

[0199] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0200] Embodiment 19

[0201] In this example, the catalyst 20% Co was prepared using carrier Z3 100 Ru 1.5 Zr 10 -80% Z3, and conduct catalytic evaluation on the catalyst, including the following processes:

[0202] 1) 84.39 g of cobalt nitrate hexahydrate, 0.894 g of ruthenium trichloride and 12.45 g of zirconium nitrate pentahydrate were dissolved in 100 mL of water to prepare a solution of a certain concentration, and then added dropwise to 80 g of the carrier Z3 prepared in Example 3 to form a mixture I, which was allowed to stand for 18 h.

[0203] 2) The mixture I was transferred to a drying oven at 100°C and dried for 12 h, and then calcined at 540°C for 4 h to obtain a catalyst 20% Co 100 Ru 1.5 Zr 10 -80% Z3.

[0204] The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 142 m 2 / g, pore volume is 0.43cm 3 / g, pore size is 29nm.

[0205] 3) The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0206] Comparative Example 1

[0207] In this comparative example, a composite carrier DZ1 was prepared and used as a carrier to prepare a catalyst 30% Co 100 -70% DZ1.

[0208] The only difference from Example 1 is that the mixed solution A contains only magnesium nitrate and titanium sulfate, and a composite carrier DZ1 is obtained.

[0209] The method of loading the active components was the same as in Example 9 to obtain a catalyst with 30% Co 100 -70% DZ1. The catalyst reduction conditions and evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0210] Comparative Example 2

[0211] In this comparative example, a composite carrier DZ2 was prepared and used as a carrier to prepare a catalyst 30% Co 100 -70% DZ2.

[0212] The only difference from Example 1 is that there is only titanium sulfate in the mixed solution A, and a composite carrier DZ2 is obtained.

[0213] The method of loading the active components was the same as in Example 9 to obtain a catalyst with 30% Co 100 -70% DZ2. The catalyst reduction conditions and evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0214] Comparative Example 3

[0215] In this comparative example, a composite carrier DZ3 was prepared and used as a carrier to prepare a catalyst 30% Co 100 -70% DZ3.

[0216] The only difference from Example 1 is that the molar number of propylene oxide is 40 times the total molar number of the added metal elements, and a composite carrier DZ3 is obtained.

[0217] The method of loading the active components was the same as in Example 9 to obtain a catalyst with 30% Co 100 -70% DZ3.

[0218] The reduction conditions of the catalyst and the evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0219] Comparative Example 4

[0220] In this comparative example, a composite carrier DZ4 was prepared and used as a carrier to prepare a catalyst 30% Co 100 -70% DZ4.

[0221] The only difference from Example 1 is that the molar number of propylene oxide is 0.7 times the total molar number of the added metal elements, and a composite carrier DZ4 is obtained.

[0222] The method of loading the active components was the same as in Example 9 to obtain a catalyst with 30% Co 100 -70% DZ4. The catalyst reduction conditions and evaluation reaction conditions are the same as those in Example 9. The specific evaluation results are shown in Table 1.

[0223] Table 1 Catalyst evaluation results

[0224]

[0225] By comparing Comparative Examples 1 to 2 with Example 9, it can be seen that the Mn-modified composite carrier has better catalytic reaction activity and higher long-chain hydrocarbon selectivity than the single carrier.

[0226] By comparing Comparative Examples 1 to 4 with Examples 9 to 19, it can be seen that the addition of metals Ru, Pt, Ir, Zr, and Nb in the active components is beneficial to further improve the reaction activity of the catalyst.

[0227] By comparing comparative examples 3 to 4 with embodiments 9 to 19, it can be seen that during the preparation of the carrier, when the molar number of propylene oxide is 1 to 15 times the total molar number of the added metal elements, the catalytic activity is higher after the active component is loaded, and beyond this range, the activity is significantly reduced.

[0228] Embodiments 20 to 25

[0229] The catalyst prepared in Example 9 was taken and the evaluation conditions were changed to evaluate the catalyst. The evaluation conditions and evaluation results are shown in Table 2.

[0230] Table 2

[0231]

[0232] It can be seen from Examples 20-25 that within the given reaction conditions, the catalytic reaction performance of the catalyst of the present invention is good.

[0233] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A cobalt-based Fischer-Tropsch catalyst, wherein: The cobalt-based Fischer-Tropsch catalyst comprises a carrier and an active component supported on the carrier; The carrier is a manganese-modified composite carrier Mn-TiO2 / MgO; The active component is generally represented by the atomic ratio: Co 100 A a B b ; wherein A is selected from at least one of Ru, Pt, and Ir, B is selected from at least one of Zr and Nb, the value range of a is 0 to 5, and the value range of b is 0 to 15.

2. The cobalt-based Fischer-Tropsch catalyst according to claim 1, wherein: In the cobalt-based Fischer-Tropsch catalyst, the mass proportion of the active component is 20% to 50%, and the mass proportion of the carrier is 50% to 80%.

3. The cobalt-based Fischer-Tropsch catalyst according to claim 1, wherein: In the manganese-modified composite carrier Mn-TiO2 / MgO, the molar ratio of manganese to magnesium is 1:(0.1-25), and the molar ratio of manganese to titanium is 1:(0.1-25).

4. The cobalt-based Fischer-Tropsch catalyst according to claim 1, wherein: The active component Co 100 A a B b In the formula, the value range of a is 0.1 to 2, and the value range of b is 5 to 10.

5. The cobalt-based Fischer-Tropsch catalyst according to claim 1, wherein: The specific surface area of ​​the cobalt-based Fischer-Tropsch catalyst is 80 to 220 m 2 / g, pore volume is 0.2~0.7cm 3 / g, pore size is 5~35nm.

6. The cobalt-based Fischer-Tropsch catalyst according to claim 1, wherein: The carrier is prepared by the following steps: Dissolving a manganese source, a magnesium source and a titanium source in an alcohol solvent to obtain a mixed solution A; After adding mesoporous silica to the mixed solution A, heating and stirring to form a mixture B; Adding an epoxy compound to the mixture B, stirring until the mixture becomes a gel, and then aging the mixture; Drying and calcining the mixture obtained by aging; The calcined solid is treated with a hot alkaline solution and centrifuged to obtain a solid C; Dissolve tetraethyl orthosilicate in an alcohol solvent to form a mixed solution D; then mix the mixed solution D with a solid substance C for immersion, and then dry and calcine to obtain a manganese-modified composite support Mn-TiO2 / MgO.

7. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The manganese source is selected from at least one of manganese nitrate and manganese acetate.

8. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The magnesium source is selected from at least one of magnesium nitrate, magnesium acetate and magnesium chloride.

9. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The titanium source is selected from at least one of titanium sulfate, butyl titanate, tetraisopropyl titanate and titanium chloride.

10. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The molar number of the epoxy compound is 1 to 15 times the total molar number of the added metal elements.

11. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The drying temperature of the mixture obtained by aging is 60-120° C., and the drying time is 6-24 hours; the calcination temperature is 550-750° C., and the calcination time is 2-4 hours.

12. The cobalt-based Fischer-Tropsch catalyst according to claim 6, wherein: The soaked solid C is dried at a temperature of 60 to 120° C. for 4 to 24 hours, and is calcined at a temperature of 400 to 750° C. for 3 to 12 hours.

13. A method for preparing the cobalt-based Fischer-Tropsch catalyst according to any one of claims 1 to 12, wherein: The preparation method comprises the following steps: Dissolve the soluble salt containing the active ingredient in deionized water to prepare a mixed solution I with a volume equal to or in excess of the water absorption of the carrier; The mixed solution I is added dropwise onto the support to form a mixture I, which is allowed to stand for drying and calcination to obtain the cobalt-based Fischer-Tropsch catalyst.

14. The preparation method according to claim 13, wherein: The cobalt source in the soluble salt containing the active component is selected from at least one of cobalt nitrate, cobalt acetate, cobalt carbonate, cobalt bicarbonate and cobalt sulfate.

15. The preparation method according to claim 13, wherein: When the active component further includes A metal and / or B metal, the soluble salt containing the active component further includes nitrate, chloride or oxalate of A metal and / or B metal.

16. The preparation method according to claim 15, wherein: When the active component further includes metal A and / or metal B, the soluble salt containing the active component further includes at least one of the following: ruthenium trichloride, chloroplatinic acid, hydrated iridium trichloride, zirconium nitrate pentahydrate, and niobium oxalate.

17. The preparation method according to claim 13, wherein: The drying temperature of the mixture I after standing is 80 to 120° C., and the drying time is 6 to 24 hours.

18. The preparation method according to claim 13, wherein: The calcination temperature of the dried mixture I is 450-600° C., and the calcination time is 2-4 hours.

19. Use of the cobalt-based Fischer-Tropsch catalyst according to any one of claims 1 to 12 in a Fischer-Tropsch synthesis reaction, wherein: The cobalt-based Fischer-Tropsch catalyst is reduced and activated by hydrogen-containing gas before use.

20. The use according to claim 19, wherein: The Fischer-Tropsch synthesis reaction is carried out in a fixed bed reactor, and the reaction conditions include: reaction temperature of 200-260°C, raw gas V(H2) / V(CO)=1.5-3, reaction pressure of 1.5-3MPa, space velocity of 800-2000h -1 .

Citation Information

Patent Citations

  • Fischer-Tropsch synthesis precipitated-iron base catalyst and preparation method and preparation thereof and method for preparing hydrocarbon compounds through synthesis gas via Fischer-Tropsch synthesis of slurry reactor

    CN107617442A

  • Application of catalyst in Fischer-Tropsch synthesis reaction

    CN113117689A

  • Preparation method of supported nanometer catalyst

    CN109847737A

  • Cobalt-based Fischer-Tropsch synthesis catalyst and preparation method thereof

    CN110270334A

  • Catalyst for synthesizing low-carbon olefin by using synthesis gas and application of catalyst to synthesis of low-carbon olefin

    CN110639495A